Factors Affecting the Management of Foreign currency of the people of Bortane and Kaenthao district at Xayyaboury Province. Case study: Foreign Currency Thai Baht.Factors Affecting the Management of Foreign currency of the people of Bortane and Kaenthao d - SENGKEO , Phonesouda; HOUNGSENGFAR, Southida; INDAVONG, Dalounny; CHANMAVONG , Aksonexay; KHATTIGHALATH, Lithigha (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objective of this study is:1) Behavior of the using foreign currency in Thai Baht by the people of Bortane and Kaenthao district at Xayaburi province, and 2) factors affecting the using of foreign currency in Thai Baht by people of Boten-Kanthao district Municipality at Xayabouly Province by questioning and surveyed 3 5 7 Peoples. The study appled Logistics Regression Model to analyze the data. The research results show that Behavior in using Thai baht currency of local people in Bortaen-Kaenthao districts is mainly caused from social value. The purpose of using Thai baht in transaction is for Thai products purchasing which is sold in the districts cover 100%. The other purpose of the behavior is for buying goods in Thai border, covering 23.05%. For emergent transaction in Thailand is covered by 15.27%. Using the Thai baht for running a business or trading in Thailand covers 12 .3 7 % . And for money exchange rate of benefit, covers the least 1.73%. The average of using Thai baht currency in transaction is 38,978.38 baht a month. The Factors affecting the using of Foreign Currency in Thai Baht by people of Botaen- Kanthao district in Xayabouly Province consist of six factors such as: 1)Average income per month, 2) Average expenditure per month, 3 ) Level of change in domestic commodity prices, 4) Level of changes in current income and future income, 5) The level of ability of the baht in foreign exchange, and 5) the growth level of the exchange facility had statistical significance at the level of 0.1.